2006
DOI: 10.3171/spi.2006.4.6.472
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical considerations for cervical pedicle screw insertion: the use of multiplanar computerized tomography reconstruction measurements

Abstract: Object The purpose of this study was to evaluate the linear and angular parameters of the vertebral body (VB) required for cervical pedicle screw (CPS) insertion by using multiplanar computerized tomography (CT) reconstructions. Methods Three hundred fifteen vertebrae from C-3 to C-7 in 63 patients were studied. Pedicle dimensions such as pedicle transverse angle (PTA), pedicle sagittal angle (PSA), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 13 publications
4
31
1
Order By: Relevance
“…Karaikovic et al investigated cervical pedicle morphology using human cadaver specimens via manual and computed tomography measurements and suggested that there were anatomical limitations associated with the use of the pedicle screw in the cervical spine [22, 23]. Chazono et al evaluated the linear and angular parameters of the cervical spine as well as pedicle dimensions required for safe CPS placement using multiplanar CT reconstruction [24]. They reported that the overall mean pedicle transverse angle (PTA) ranged from 33.6 to 50.2° and that the smallest mean PTA was found at C7 in males (33.4°) and in females (34.1°); the largest mean PTA was found at C4 in males (50.4°) and in females (49.6°) followed by C5, C3, and C6.…”
Section: Discussionmentioning
confidence: 99%
“…Karaikovic et al investigated cervical pedicle morphology using human cadaver specimens via manual and computed tomography measurements and suggested that there were anatomical limitations associated with the use of the pedicle screw in the cervical spine [22, 23]. Chazono et al evaluated the linear and angular parameters of the cervical spine as well as pedicle dimensions required for safe CPS placement using multiplanar CT reconstruction [24]. They reported that the overall mean pedicle transverse angle (PTA) ranged from 33.6 to 50.2° and that the smallest mean PTA was found at C7 in males (33.4°) and in females (34.1°); the largest mean PTA was found at C4 in males (50.4°) and in females (49.6°) followed by C5, C3, and C6.…”
Section: Discussionmentioning
confidence: 99%
“…This diameter allows at least 0.5 mm bony bridge medially and laterally in order to avoid pedicle violation which can result in neurovascular complications [1, 12, 16, 22, 23]. Based on data from previous reports and our current study, the OPW is considered to be the most important parameter in assessing the feasibility of the TPSF technique [1, 2, 9, 12, 24, 25]. This is because the OPH is larger than the width.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these measurements, the interpedicular distance (IPD) was also measured. The pedicle sagittal angle was not measured in our current study because of the variation in the technique of measuring this angle among previous investigators making it an unreliable measure [912]. …”
Section: Methodsmentioning
confidence: 99%
“…Anatomical considerations for the safety and accuracy of the cervical pedicle screw For accurate and safe subaxial CPS placement, surgeons should understand the detailed threedimensional (3D) morphology of the pedicle. With regard to reports on the morphology of the cervical pedicle, [17][18][19][20][21][22][23] the measured parameters including pedicle transverse angle (PTA) and pedicle outer width (POW) are indicated in Fig. 2A.…”
Section: Selection Of Reference Articlesmentioning
confidence: 99%
“…The smallest mean POW of 4.5 mm was obtained at C3, with gradual increases in the mean value caudally from C3 to C7. 17,22) Karaikovic et al 24) reported that if the POW is sufficiently large, a canal of adequate size can be made with an appropriate tap, regardless of the pedicle inner width. Abumi et al 25) used 3.5-4.5-mm diameter screws and reported that screw insertion was difficult or impossible in cases with a POW of <4 mm; whereas, Park et al 26) used 3.5-4.5-mm diameter pedicle screws in cases with a POW of >3 mm on axial computed tomography (CT) scan.…”
Section: Selection Of Reference Articlesmentioning
confidence: 99%